Bacterial Protein Tyrosine Phosphatases as Possible Targets for Antimicrobial Therapies in Response to Antibiotic Resistance - Alicja Kuban-Jankowska; Tomasz Kostrzewa; Magdalena Gorska-Ponikowska (Antioxidants, 2022)
The review is focused on the bacterial protein tyrosine phosphatases (PTPs) utilized by bacteria as virulence factors necessary for pathogenicity. The inhibition of bacterial PTPs could contribute to the arrest of the bacterial infection process. This mechanism could be utilized in the design of antimicrobial therapy as adjuvants to antibiotics. The review summaries knowledge on pathogenic bacterial protein tyrosine phosphatases (PTPs) involved in infection process, such as: PTPA and PTPB from Staphylococcus aureus and Mycobacterium tuberculosis; SptP from Salmonella typhimurium; YopH from Yersinia sp. and TbpA from Pseudomonas aeruginosa. The review focuses also on the potential inhibitory compounds of bacterial virulence factors and inhibitory mechanisms such as the reversible oxidation of tyrosine phosphatases.